The Effect Of Product Quality And Packaging On Brand Image (Survey On Consumers Crispy Baby Fish Mr. O Tasikmalaya) - Ajeng Kurniasari; Depy Muhamad Pauzy; Suci Putri Lestari (Journal of Indonesian Management, 2022)
This study aims to determine the effect of product quality and packaging on brand image on crispy baby fish Mr.O Tasikmalaya'sThe method used in this research is a quantitative approach with a survey method. The population in this study is unknown and the sample is taken using Nonprobability Sampling. While determining the number of respondents (samples) using the Incidental Sampling method as many as 100 respondents. The analytical tool used is multiple regression analysis. SPSS version 25 is used.  The results showed that product quality and packaging simultaneously had a significant effect on brand image. Partially product quality has a significant influence on brand image. Partially, packaging has a significant effect on brand image.